The Role Of Information Society In The Development Of Farhangian University - Soltaninejad, Amir; Poour, Muhammad Ali Yaghoubi; Sadei, Ali; Saadatzadeh, Majid; Gohari, Masoumehossadat Mirzadi (The Turkish Online Journal of Design Art and Communication, 2016)
In this study, we attempted to examine the role of information society in the development of Farhangian University. The research method is descriptive-survey. The population of this study, being 145 peoplewas consisted of experts, staff and faculty members of Farhangian University of Kerman -in the academic year of 2014-2015. Access was possible to all members of the community and a list of available people was made. Using census methods, 145 people were selected as samples of the study among the staff and faculty members of Farhangian University. A research made questionnaire, having an optimal reliability and validity (α= 0.88), was used in the study. Since the aim of this study was to evaluate the impact of the information society on the development of Farhangian University, a five-component scale was implemented; planning, organization, command, coordination and control. To test the hypotheses (rejection or acceptance) one- sample t test was used. The results indicated that experts, professors and staff of Farhangian University of Kerman believed that the role of the information society in the development of the university is at an average level in terms of planning and organizing; however, in terms of command, coordination and control, the role of the information society was lower than expected.
Keywords: information society; Farhangian University; planning; organization; command